Model Penjaminan Mutu Sumber Daya Manusia di Pesantren: Pendekatan Supply Demand and Resourcing Strategy - Sya'bana, Azka; Siregar, Maragustam; Hasyim, A Dardiri (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This study aims to address the gap in human resource management within Islamic boarding schools (pesantren) by developing a quality assurance model based on supply and demand estimation and resourcing strategy. It evaluates the model's effectiveness and its potential to modernize pesantren while preserving their core values.Method – This study Utilizing a research and development (R&D) approach, this study combines qualitative and quantitative methods to develop and test the model. Data were collected through interviews, questionnaires, and observations, analyzed using descriptive statistics and interval calculations to measure effectiveness.Findings – This study demonstrates that the human resource quality assurance model based on supply and demand estimation at Pondok Pesantren Al Jauhar is effective in improving HR quality, relevant, and flexible in addressing modernization challenges without neglecting traditional pesantren values. Research Implications – This study implies the need for reorienting human resource development, enhancing motivation, integrating technology into management, and conducting continuous evaluations.